2015
DOI: 10.4038/cjsbs.v44i1.7339
|View full text |Cite
|
Sign up to set email alerts
|

Moss Flora of Kanneliya Forest Reserve, Sri Lanka

Abstract: Bryophytes; liverworts, mosses and hornworts, comprise an important yet poorly researched group of plants in Sri Lanka. Varied climate and topography of the island provide ample habitat diversity for bryophytes. However, the diversity and species richness of the three morphological groups of bryophytes within the country are yet to be discovered. Kanneliya Forest Reserve, a prominent lowland rain forest in the wet zone of Sri Lanka has been a base for much scientific research on both flora and fauna. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Recent field explorations and taxonomic studies have identified a few new records to the island: Tan (2005) -five new species records of mosses; Ruklani and Rubasinghe (2013) -10 new records of mosses and liverworts. Also, studies are being carried out to investigate the bryoflora of different ecosystems of the country (Ruklani and Rubasinghe, 2015). These studies will contribute to elucidating the biogeographic affinities of Sri Lanka.…”
Section: Resultsmentioning
confidence: 99%
“…Recent field explorations and taxonomic studies have identified a few new records to the island: Tan (2005) -five new species records of mosses; Ruklani and Rubasinghe (2013) -10 new records of mosses and liverworts. Also, studies are being carried out to investigate the bryoflora of different ecosystems of the country (Ruklani and Rubasinghe, 2015). These studies will contribute to elucidating the biogeographic affinities of Sri Lanka.…”
Section: Resultsmentioning
confidence: 99%
“…Hot and humid climate with annual rainfall over 2,500 mm makes this island home to different varieties of bryophytes, and most of them are endemic and native [ 8 , 9 ]. There are over 200 recorded species of bryophytes in Sri Lanka, and most of them are found in tropical rain and submontane and montane forests [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The island is one of the most diverse regions in South Asia and is recognized as one of the world's biodiversity hotspots along with the Western Ghats of India (Ashton et al, 1997). Owing to its high level of topographic and climatic heterogeneity, Sri Lanka supports a luxuriant growth of a remarkably rich bryophyte (liverworts, mosses, hornworts) flora (Geffert et al, 2013;O'Shea, 2003;Ruklani and Rubasinghe, 2015). In contrast to the wellstudied higher plant flora of Sri Lanka, bryophytes are still poorly explored, mainly due to their small size and difficult taxonomy (O'Shea, 2003;Rubasinghe and Long, 2014;Ruklani and Rubasinghe, 2013;Ruklani and Rubasinghe, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its high level of topographic and climatic heterogeneity, Sri Lanka supports a luxuriant growth of a remarkably rich bryophyte (liverworts, mosses, hornworts) flora (Geffert et al, 2013;O'Shea, 2003;Ruklani and Rubasinghe, 2015). In contrast to the wellstudied higher plant flora of Sri Lanka, bryophytes are still poorly explored, mainly due to their small size and difficult taxonomy (O'Shea, 2003;Rubasinghe and Long, 2014;Ruklani and Rubasinghe, 2013;Ruklani and Rubasinghe, 2015). According the recent checklists, the island harbours 327 species of liverworts (Long and Rubasinghe, 2014), 560 mosses (O'Shea, 2002) and five Hornworts (Long and Rubasinghe 2014).…”
Section: Introductionmentioning
confidence: 99%